环AMP反应元件结合蛋白(CBP)和/或300KDA腺病毒E1A结合蛋白(P300)降解化合物和使用方法 (2025)
本发明涉及二价化合物(例如双功能小分子化合物)，含有一种或多种二价化合物的组合物，以及在需要的对象中使用二价化合物治疗某些疾病的方法，以及鉴定这种二价化合物的方法。 Provided are bivalent compounds (e.g., bi-functional small molecule compounds), compositions comprising one or more of the bivalent compounds, and methods of use the bivalent compounds for the treatment of certain disease in a subject in need thereof, and methods for identifying such bivalent compounds.